29 Investigating the population characteristics, processes and outcomes of pre-hospital psychiatric and self-harm emergencies in scotland: a national record linkage study. (21st May 2017) - Duncan, E; Best, C; Dougall, N; Skar, S; Fitzpatrick, D; Evans, J; Corfield, A; Goldie, I; Maxwell, M; Snooks, H; Stark, C; White, C; et al.
Abstract : Aim: To investigate the demographic characteristics, care pathways, and clinical and service outcomes of people who present to ambulance services with a psychiatric or self-harm emergency Methods: We conducted a retrospective cohort study of patients attended by the Scottish Ambulance Service in 2011 with ambulance clinician attendance codes relating to 'psychiatric emergency' or 'self-harm'. Patients resident in Scotland and>=16 years on first contact were included. We used NHS Scotland's Unscheduled Care Data Mart (1) to link data from: – the ambulance service; emergency departments (ED); general and psychiatric inpatient hospital admissions episodes; and death records. Results: There were 9014 calls from 6802 people. Slightly more males (n=4708, 52%) than females (n=4306, 48%) were attended. Most were discharged from ED with no known follow-up (n=4566; 51%). Some were left at home (n=1003 attendances, 11%). Almost half of the people (n=3238, 48%) made at least one repeat call. People who self-discharge from ED were more likely to have another ambulance attendance for psychiatric emergency/self-harm within the same year (Pearson chi square=5.24, p=0.02). Two hundred and seventy-nine (4%) people died within the study period, 97 (35%) were recorded as suicide. Ethical approval (NRES 15/EM/0260) and other data approvals were received. Conclusion: While linked data analysis may not identify all relevant cases, it provides important information to guide the development and evaluation of evidence-based interventions. Ambulance service and ED are missing opportunities to improve outcomes for people who experience a psychiatric emergency or who self-harm. New interventions could lead to decreases in the number of suicides, episodes of self-harm and levels of patient distress; and ambulance and ED service use. Reference: Information Services Division (NHS Scotland) (2016) Unscheduled Care Datamart Background Paper. Accessible at http://www.isdscotland.org/Health-Topics/Emergency-Care/Patient-Pathways/unscheduledcare_background.pdf Accessed on 13/01/17 Conflict of interest: None declared. Funding: Scottish Government, Chief Scientists Office